Mobile-Based Archipelago Tourist Destination UI/UX Design as Information Media for Archipelago Tourists: Desain UI/UX Destinasi Wisata Nusantara Berbasis Mobile sebagai Media Informasi bagi Wisatawan Nusantara - Siti Masyithoh; Pratama Bayu, Widagdo (Arty: Jurnal Seni Rupa, 2024)
The National Medium Term Development Plan (RPJMN) 2020-2024 shows that 41 percent of Indonesian tourism still relies on Bali, even though Indonesia has a variety of other tourist destinations that can be exposed. This is due to the lack of information about less popular tourist destinations, thereby limiting exposure to these destinations. This study project aims to produce a mobile-based UI/UX design using a design thinking framework. The result is a UI/UX design prototype "triv" which includes tourist recommendation features, search bar, filter, share, reviews, community, explore, and tourist map. Testing the “triv” UI/UX design prototype using the maze site and the System Usability Scale (SUS) questionnaire to measure the level of user acceptance. The overall SUS score for 15 respondents was 79.3 so the score was in the > 68 percentile, meaning that the UI/UX design of the triv was above average, getting grade A- in the grades scale interpretation, good in the adjective rating category , and the acceptable category in the interpretation ofacceptability. This shows that the design is well received by users, and has the potential to be promoted further based on the interpretation of the Net Promoter Score (NPS).